2006
DOI: 10.1038/nature05125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a mammalian mitochondrial porphyrin transporter

Abstract: The movement of anionic porphyrins (for example, haem) across intracellular membranes is crucial to many biological processes, but their mitochondrial translocation and coordination with haem biosynthesis is not understood. Transport of porphyrins into isolated mitochondria is energy-dependent, as expected for the movement of anions into a negatively charged environment. ATP-binding cassette transporters actively facilitate the transmembrane movement of substances. We found that the mitochondrial ATP-binding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
428
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(455 citation statements)
references
References 27 publications
17
428
1
9
Order By: Relevance
“…This observation is relatively consistent with recent reports of growth and proliferation defects associated with loss of Abcb6 function in humans and in zebrafish (22). Although Abcb6 is capable of transporting heme precursors into the mitochondria (17,18) and plays a role in regulating porphyrin synthesis in vitro (17,26), Abcb6 deficiency in vivo did not have a significant impact on hepatic porphyrin or heme levels. This suggests that in vivo Abcb6 might not be important for basal porphyrin synthesis.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This observation is relatively consistent with recent reports of growth and proliferation defects associated with loss of Abcb6 function in humans and in zebrafish (22). Although Abcb6 is capable of transporting heme precursors into the mitochondria (17,18) and plays a role in regulating porphyrin synthesis in vitro (17,26), Abcb6 deficiency in vivo did not have a significant impact on hepatic porphyrin or heme levels. This suggests that in vivo Abcb6 might not be important for basal porphyrin synthesis.…”
Section: Discussionsupporting
confidence: 81%
“…1f). These results suggest that although Abcb6 is capable of transporting heme precursors into the mitochondria (18,27) and plays a role in regulating porphyrin synthesis in vitro (17,18,26), Abcb6 deficiency in vivo does not have a significant impact on basal hepatic porphyrin or heme levels. These findings are consistent with recent reports that demonstrate a lack of functional association between Abcb6 and basal porphyrin synthesis in erythroid cells in vivo (18).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The enzyme receiving CPgenIII, coproporphyrinogen oxidase (CPOX), is anchored on the mitochondrial matrix with the active site in the intermembrane space [62]. ABCB6 was proposed to be responsible for transporting CPgenIII across the mitochondrial outer membrane [63]. However, a more recent study revealed that ABCB6 specifies the blood group Langereis and is not required for erythropoiesis [64].…”
Section: Transport Of Heme Synthesis Intermediatesmentioning
confidence: 99%